Conceito de derivada: uma proposta para seu ensino e aprendizagem - Dall'Anese, Claudio (2000)
Since difficulties exist, in refering to the teaching and lerning of Differential and Integral Calculus, this work presents a didactic sequence with activities allocated in records, in which the students work in couples to perceive the essence of the concept of derivatives. After the resolution of each record, it is settled down a plenary to discuss the presented answers. The choice of this methodological practice represents a rupture of the habitual didactic contract. I present a posteriori analysis of each record, confronting the student s protocols with a priori analysis. This allows to raise conclusions about the gains of this pedagogic choice to the teaching and learning of the concept of the derivative